(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Background: Infants of diabetic mother are those born to mother who has persistently elevated blood sugar during pregnancy. It causes fetal hyperglycemia, which contributed to many complications happen on those infants. This study aims To show the outcome of infants of diabetic mothers. Methods: the study included 100 infant born to diabetic mothers in the period between 1st. April 2015 to 17th. August 2016 . multiple clinical, biochemical and radiographic assessments was done to them to discover any complication. The results then are compared between infants of treated to non-treated mothers using SPSS software. Results: the study found that infants of non-treated diabetic mothers show higher percentage of complications in comparison to those treated mothers like Hypoglycemia 83%, hypocalcemia 5% and no hypomagnesemia in treated mothers group while in untreated mothers show 94% hypoglycemia, 29% hypocalcemia and hypomagnesemia 17%. Also the study found higher percentage of respiratory, cardiac, neurological and genito-renal complication in neonates of non-treated infants compared to treated one. Conclusion: Higher clinical &biochemical complications are seen in neonates of non- treated mothers or poorly control diabetes. Most teratogenic complications occur in infants born to mothers with diabetes that is poorly controlled.